As Soft Skills no mercado de trabalho da indústria 4.0 - Martinello, Tamara (Universidade do Vale do Rio dos Sinos, 2022)
With the rise of technology in Industry 4.0, many processes have changed and been adapted to this new reality. By adding value where it is present, technology started to be in several sectors, no longer being specific only for those who deal with information technology and its aspects. From then on, not only the processes had to experience changes, but also the work professional. Inserted in a new context, professionals from all areas were challenged to keep their jobs and not be easily replaced by technology. In a highly technological scenario, we usually might think that professionals, during their trajectories in their jobs, should be technically prepared for their work. However, despite seeming a bit contradictory, the more technology has gained space in our lives, the more it is noticed that soft skills are becoming as important, if not more, than technical skills in the job market. Based on this finding, a Literature Review was carried out on the importance of soft skills in industry 4.0, to identify how and which skills can help professionals in this new context that is rapidly arriving in our society.
Keywords: Indústria 4.0; Profissionais; Soft Skills; Gestão de pessoas; Empregos; Industry 4.0; Professionals; People management; Jobs